Mitigating Disinformation: Reflection of #NoNotAgain Campaign in Nepal for Indonesia - Candra Kresna Wijaya; Kent Revelino Chandra; I Komang Dananjaya (Uti Possidetis: Journal of International Law, 2024)
Ahead of election day in Nepal, a #NoNotAgain campaign movement has emerged on facebook advocating people not to vote for some incumbent prime ministerial candidates. The campaign criticized the candidates' failures during their previous terms in office. Nepal Election Commission then reacted by demanding that the facebook page be shut down through the threat of imprisonment or fines. With a normative legal research method that uses statutory, factual, conceptual, and comparative approaches, this article is prepared with the aim of analyzing the legality of the Nepal Election Commission restriction efforts on the freedom of expression of Nepalese through the restriction requirements contained in the International Covenant on Civil and Political Rights. Given that this phenomenon is related to the conditions that Indonesia will face in the 2024 general election, therefore, this article also seeks to find the ideal formulation of disinformation mitigation mechanism while respecting freedom of expression. The results of this study show that the response of Nepal Election Commission has violated freedom of opinion and expression. By reflecting on Nepal's experience, Indonesia can employ several alternative methods in dealing with disinformation.